Search for tt[bar]H/A → tt[bar] tt[bar] production in proton-proton collisions √s=13TeV with the ATLAS detector - Aad, Georges; Ackermann, Anke; Baltes, Lisa Marie; Bartels, Falk; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Junkermann, Thomas; Mkrtchyan, Tigran; Sanfilippo, Lorenzo; Sauer, Christof; Schöning, André; et al. (The European physical journal. C, Particles and fields, 2025)
A search is presented for a heavy scalar (H) or pseudo-scalar (A) predicted by the two-Higgs-doublet models, where the H/A is produced in association with a top-quark pair (tt[bar]H/A), and with the H/A decaying into a tt[bar] pair. The full LHC Run 2 proton-proton collision data collected by the ATLAS experiment is used, corresponding to an integrated luminosity of 139 fb -1. Events are selected requiring exactly one or two opposite-charge electrons or muons. Data-driven corrections are applied to improve the modelling of the tt[bar]+jets background in the regime with high jet and b-jet multiplicities. These include a novel multi-dimensional kinematic reweighting based on a neural network trained using data and simulations. An H/A-mass parameterised graph neural network is trained to optimise the signal-to-background discrimination. In combination with the previous search performed by the ATLAS Collaboration in the multilepton final state, the observed upper limits on the tt[bar]H/A → tt[bar] tt[bar] production cross-section at 95% confidence level range between 14 fb and 5.0 fb for an H/A with mass between 400 GeV and 1000 GeV, respectively. Assuming that both the H and A contribute to the tt[bar] tt[bar] cross-section, tan beta values below 1.7 or 0.7 are excluded for a mass of 400 GeV or 1000 GeV, respectively. The results are also used to constrain a model predicting the pair production of a colour-octet scalar, with the scalar decaying into a tt[bar] pair.